Ancestral androgenic differentiation pathways are repurposed during the evolution of adult sexual plasticity. Issue 5 (10th November 2016) - Schuppe, Eric R.; Solomon‐Lane, Tessa K.; Pradhan, Devaleena S.; Thonkulpitak, Kevin; Grober, Matthew S.
SUMMARY: Although early exposure to androgens is necessary to permanently organize male phenotype in many vertebrates, animals that exhibit adult sexual plasticity require mechanisms that prevent early fixation of genital morphology and allow for genital morphogenesis during adult transformation. In Lythrypnus dalli, a teleost fish that exhibits bi‐directional sex change, adults display dimorphic genitalia morphology despite the absence of sex differences in the potent fish androgen 11‐ketotestosterone. Based on conserved patterns of vertebrate development, two steroid‐based mechanisms may regulate the early development and adult maintenance of dimorphic genitalia; local androgen receptor (AR) and steroidogenic enzyme expression. Consistent with the ancestral pattern of AR expression during the multipotential phase of differentiation, juvenile differentiation into either sex involved high mesenchymal AR expression. In adults, AR expression was high throughout the male genitalia, but low or absent in females. Consistent with the hypothesis that adult sexual plasticity repurposes pathways from primary differentiation, we show that adults with transitioning genitalia also exhibited higher AR expression relative to females. Local androgen biosynthesis may also participate in genitalia transformation, as transitioning adults had greater 11β‐HSD‐like immunoreactivity in the epithelial layer of the dorsal lumen compared to both sexes. By administering an AR antagonist to adult males, we show AR is necessary to maintain male‐typical morphology. In a species that is resistant to early sexual canalization, early androgenic differentiation mechanisms are consistent with other vertebrates and the tissue‐specific regulation of AR expression appears to be repurposed in adulthood to allow for transitions between sexual phenotypes.